Gregorio de Nisa, arquitecto y empresario: Epístola 25 - Teja, Ramón (Antigüedad y Cristianismo, 1991)
This is a translation of the EPISTOLA 25 of Saint Gregory of Nisa, which contains a beautiful study of the religious architecture in the Christian Orient and also of the economic and social history of the Late Roman Empire.